Association mapping for important agronomic traits in wild and cultivated Vigna species using cross-species and cross-genera simple sequence repeat markers - Kumari, Gita; Shanmugavadivel, P. S.; Lavanya, G. Roopa; Tiwari, Pravin; Singh, Dharmpal; Gore, P. G.; Tripathi, Kuldeep; Madhavan Nair, Ramakrishnan; Gupta, Sanjeev; Pratap, Aditya (Frontiers in Genetics, 2022)
The genus Vigna is an agronomically important taxon, with many of its species inhabiting a wide range of environments and offering numerous useful genes for the improvement of the cultivated types. The present study aimed to detect the genomic regions associated with yield-attributing traits by genome-wide association mapping. A diverse panel of 98 wild and cultivated Vigna accessions (acc.) belonging to 13 different species was evaluated for yield and related traits during the kharif season of 2017 and 2018. The panel was also genotyped using 92 cross-genera and cross-species simple sequence repeat markers to study the population genetic structure and useful market-trait associations. The PCA and trait correlation established relationships amongst the traits during both seasons while 100-seed weight (HSW) had a positive correlation with pod length (PL), and days to first flowering (DFF) with days to maturity (DM). The population genetic structure analysis grouped different acc. into three genetically distinct sub-populations with SP-1 comprising 34 acc., SP-2 (24 acc.), and SP-3 (33 acc.) and one admixture group (7 acc.). Mixed linear model analysis revealed an association of 13 markers, namely, VR018, VR039, VR022, CEDG033, GMES0337, MBSSR008, CEDG220, VM27, CP1225, CP08695, CEDG100, CEDG008, and CEDG096A with nine traits. Seven of the aforementioned markers, namely, VR018 for plant height (PH) and terminal leaflet length (TLL), VR022 for HSW and pod length (PL), CEDG033 for DFF and DM, MBSSR008 for DFF and DM, CP1225 for CC at 30 days (CC30), DFF and DM, CEDG100 for PH and terminal leaflet length (TLL), and CEDG096A for CC30 and chlorophyll content at 45 days were associated with multiple traits. The marker CEDG100, associated with HSW, PH, and TLL, is co-localized in gene-encoding histone–lysine N-methyltransferase ATX5. Similarly, VR22, associated with PL and HSW, is co-located in gene-encoding SHOOT GRAVITROPISM 5 in mungbean. These associations may be highly useful for marker-assisted genetic improvement of mungbean and other related Vigna species.